To solve the quadratic equation using the factoring method, we first need to write the equation in standard form, which is \( ax^2 + bx + c = 0 \).
Given the equation:
\[ 3x^2 - x = -7x \]
We start by moving all terms to one side of the equation:
\[ 3x^2 - x + 7x = 0 \]
Combining like terms gives us:
\[ 3x^2 + 6x = 0 \]
Now, we can factor out the greatest common factor (GCF):
\[ 3x(x + 2) = 0 \]
Now, we can set each factor equal to zero:
- \( 3x = 0 \)
- \( x + 2 = 0 \)
Solving these equations:
-
From \( 3x = 0 \): \[ x = 0 \]
-
From \( x + 2 = 0 \): \[ x = -2 \]
Therefore, the roots of the quadratic equation are:
\[ x = 0, -2 \]
So the final answer is:
\[ \boxed{0, -2} \]